Valores Morais: comparando telenovelas (décadas de 1980 e 2010) - Santos, Julian Bruno Gonçalves (2014)
The aim of this study was to analyze a soap opera of 2010s, using the Lawrence Kohlberg s typology of moral values, and compare these results with a similar analysis done in three consecutive soap operas of the 1980s. Two studies were conducted: the first consists of the analysis of moral values conveyed by the soap opera Avenida Brasil (2012) and the second consists of a comparison of the results obtained in this analysis with those obtained in the analysis of the 1980s soap operas. The sample was composed of 90 chapters of the soap opera Avenida Brasil (2012) and the results of Camino e Cavalcanti (1998). For the analysis, three classifications were made: 1) according to Kohlberg's moral stages, 2) according to the intentions (Purpose) which issued the characters and the actions planned or undertaken to achieve this porpose (tactics) and 3) in accordance with the agreement, which is the appreciation, protection, acceptance and issuance of a certain moral reasoning, and the unconformity, which are transgressed behaviors and utterances that demonstrate a criticism, disagreement or rejection use of certain type of morality. The data were subjected to content analysis of Bardin (2010). The results of the first study showed that the most conveyed moral values by Avenida Brasil (2012) were those corresponding to stages 1 and 2; disagreements were related to higher stages - 4:05; purposes values were categorized in stages 1 and 2 and means values focused on actions that are committed against the other. The results of the second study showed that both the Avenida Brasil as soap operas of the 1980s, had higher frequencies related to lower stages - 1 , 2 - while the lower frequencies corresponded to higher stages - 3a, 3c , 4 5 [3] , 5 and 6. The soap opera Avenida Brasil (2012) showed a higher percentage values for stage 1 and stage 2, while the soap operas of the 1980s had a higher percentage of the values for stage 3a, 3c, 4, 5 and 5[3]. The agreement with stages 1, 2 and 3a was very high as soap opera Avenida Brasil as in the soap operas of 1980s. As for disagreements, the soap opera Avenida Brasil stands out in relation to the stages 3a and 4 and the soap operas of the 1980s in relation to stages 2, 3c, 5 [3] and 5. The soap opera Avenida Brasil had a higher percentage for purposes connected with the stage 1 and 3 conventional, while the soap operas of the 1980s have higher percentages of purposes related to stages 2, 3 affective, 4 and 5; Results showed that in the soap opera Avenida Brasil actions against others got higher percentage compared to soap operas of the 1980s. These, however, had more shares to the other and also more actions in defense of conventions or laws. It is believed that the social context in which the soap operas of the 1980s were created may have influenced the placement of more advanced moral content, since this was a period of social, political and economic openness. In the soap opera Avenida Brasil (2012), we find the author's intention in highlighting the theme of revenge, emphasizing the law into their own hands and this may be related to a public outcry for legality with emphasis on punishment and that this may have contributed to the propagation of lower moral values.